Role of the IL-6 Gene in the Etiopathogenesis of Idiopathic Scoliosis. (23rd June 2015) - Nikolova, Svetla; Dikova, Milka; Dikov, Dobrin; Djerov, Assen; Dzhebir, Gyulnas; Atanasov, Ventseslav; Savov, Alexey; Kremensky, Ivo
Abstract : Scoliotic human nuclei pulposi can respond to exogenous proinflammatory stimuli by secreting increased amounts of interleukin-6 (IL-6). The G/C polymorphism of the promoter region of IL-6 gene influences levels and functional activity of the IL-6 protein. We conducted a case-control study of eighty patients with idiopathic scoliosis (IS) and one hundred sixty healthy unrelated gender-matched controls trying to investigate the association between IS and the IL-6 promoter polymorphism at -174 position (rs1800795 G/C) in Bulgarian population. Molecular detection of the IL-6 genotypes was performed by amplification followed by restriction technology. The statistical analysis was performed by Pearson's chi-squared test. Our case-control study revealed a statistically significant association between the IL-6 (-174 G/C) functional polymorphism and susceptibility to IS. In addition, a significant association between the IL-6 (-174 G/C) polymorphism and curve severity was detected. IL-6 gene could be considered as susceptibility and modifying factor of idiopathic scoliosis. The identification of molecular markers with diagnostic and prognostic value could be useful for early detection of children at risk for the development of scoliosis and for prognosis of the risk for a rapid deformity progression. That would facilitate the therapy decisions and early stage treatment of the patient with the least invasive procedures.